1994
DOI: 10.1021/ac00079a033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Resolving Power and Separation Time in Thermal Field-Flow Fractionation, Hydrodynamic Chromatography, and Size-Exclusion Chromatography

Abstract: Comparison of resolving power and separation time in thermal field-flow fractionation, hydrodynamic chromatography, and size-exclusion chromatography. Stegeman, G.; van Asten, A.C.; Kraak, J.C.; Poppe, H.; Tijssen, R. Published in: Analytical Chemistry DOI:10.1021/ac00079a033Link to publication Citation for published version (APA):Stegeman, G., van Asten, A. C., Kraak, J. C., Poppe, H., & Tijssen, R. (1994). Comparison of resolving power and separation time in thermal field-flow fractionation, hydrodynamic chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…This gives versatility in terms of selecting the carrier composition to favor colloidal stability, thus minimizing wall and membrane interactions and particle-particle interactions. Stegeman et al (1994) compared the resolving power and separation time in thermal field-flow fractionation (TFFF), hydrodynamic chromatography and size exclusion chromatography for the size separation of polymers, and concluded that TFFF theoretically has the best separation potential due to high selectivity, but this may not be exploitable in practice owing to the technical requirements. On the other hand, SEC was found to be the fastest method for low molecular masses (Stegeman et al 1994).…”
Section: Chromatography and Related Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This gives versatility in terms of selecting the carrier composition to favor colloidal stability, thus minimizing wall and membrane interactions and particle-particle interactions. Stegeman et al (1994) compared the resolving power and separation time in thermal field-flow fractionation (TFFF), hydrodynamic chromatography and size exclusion chromatography for the size separation of polymers, and concluded that TFFF theoretically has the best separation potential due to high selectivity, but this may not be exploitable in practice owing to the technical requirements. On the other hand, SEC was found to be the fastest method for low molecular masses (Stegeman et al 1994).…”
Section: Chromatography and Related Techniquesmentioning
confidence: 99%
“…Stegeman et al (1994) compared the resolving power and separation time in thermal field-flow fractionation (TFFF), hydrodynamic chromatography and size exclusion chromatography for the size separation of polymers, and concluded that TFFF theoretically has the best separation potential due to high selectivity, but this may not be exploitable in practice owing to the technical requirements. On the other hand, SEC was found to be the fastest method for low molecular masses (Stegeman et al 1994). In general, FFF and HDC have a wider dynamic size range than SEC, while SEC has higher separation efficiency (less peak broadening).…”
Section: Chromatography and Related Techniquesmentioning
confidence: 99%
“…However, due to the high mass selectivity of ThFFF [43] the molecular mass distribution of the sample that is analyzed will usually also contribute significantly to the peak width of the observed signal. If each SEC fraction can be represented by a block function with a width corresponding to a change in the molecular diffusion coefficient of AD (this is only a simplification as polymer concentration can change within the time needed to collect a fraction), the standard deviation caused by the sampling process, expressed in units of molecular diffusion, is equal to [44] …”
Section: Calculation Of Maximum Fraction Widthmentioning
confidence: 99%
“…12 [with P(/~) ~./~ -1] could be employed to obtain the/L values of the fractions. The mass selectivity can be rearranged to [43]: ' Calculated with b = 0.564 [47].…”
Section: Test Of the Sec Sampling Processmentioning
confidence: 99%
“…1). In [7]- [9] it was shown that this principle could be used for chromatographic separations in fused silica capillaries with inner diameters in the micrometer range. Unfortunately, detection suffered from the low signal levels generated in the small detection volume.…”
Section: Integration With On-chip Hydrodynamic Chromatographymentioning
confidence: 99%